2011
DOI: 10.1111/j.1601-183x.2011.00708.x
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin receptor 2A gene moderates the effect of childhood maternal nurturance on adulthood social attachment

Abstract: The ability to form and maintain attachment relations with other people is crucial for mental health and wellbeing. The origins of attachment behaviors are often assumed to be in early experiences with other people, especially with primary caregivers. Preliminary evidence suggests that serotonergic system may be involved in attachment behaviors. We examined whether the T102C variant of the serotonin receptor 2A gene moderates the effect of childhood maternal nurturance on social attachment in adulthood. The pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 58 publications
(80 reference statements)
3
26
1
Order By: Relevance
“…For the subscales of RAAS, although ANOVA with subscales as a within-participant factor and genotype as a between-participant factor did not find a significant main effect of genotype, F(1,492) = 1.542, p = .215, given the previous studies showing that individual differences in attachment orientation are modulated by HTR2A and 5-HTT variations (Caspers et al, 2009;Gillath et al, 2008;Salo et al, 2011), we tentatively conducted t-tests for the scores on the three subscales to examine the effect of genotype on attachment orientation. For the close subscale, individuals with the CC genotype (3.62 ± .58) reported higher scores than individuals with the CG/GG genotype (3.51 ± .57), t(502) = 2.142; uncorrected p = .033, Bonferroni-adjusted p = .098, Cohen's d = −.19 (Fig.…”
Section: Attachment Testcontrasting
confidence: 53%
See 1 more Smart Citation
“…For the subscales of RAAS, although ANOVA with subscales as a within-participant factor and genotype as a between-participant factor did not find a significant main effect of genotype, F(1,492) = 1.542, p = .215, given the previous studies showing that individual differences in attachment orientation are modulated by HTR2A and 5-HTT variations (Caspers et al, 2009;Gillath et al, 2008;Salo et al, 2011), we tentatively conducted t-tests for the scores on the three subscales to examine the effect of genotype on attachment orientation. For the close subscale, individuals with the CC genotype (3.62 ± .58) reported higher scores than individuals with the CG/GG genotype (3.51 ± .57), t(502) = 2.142; uncorrected p = .033, Bonferroni-adjusted p = .098, Cohen's d = −.19 (Fig.…”
Section: Attachment Testcontrasting
confidence: 53%
“…Alexithymia and the insecure attachment orientation have overlapping psychological symptoms and etiology, both having difficulties in describing feelings, regulating emotions, and dealing with social or interpersonal situations (Davis et al, 2003;Benetti et al, 2010;Towler and Stuhlmacher, 2013) and both with traumatic childhood experiences as one cause of these difficulties (Wearden et al, 2003). Given these associations and given the finding that individual differences in attachment orientation are modulated by genetic variations, such as rs6313 in serotonin receptor 2A (Gillath et al, 2008;Salo et al, 2011), 5-HTTLPR of serotonin transporter (Caspers et al, 2009), and TaqIA in dopamine receptor 2 (Gillath et al, 2008), a secondary purpose of this study was to investigate whether the C-1019G polymorphism in 5-HT1A affects attachment orientation, with individuals having the G allele showing increased insecure orientation than individuals having the C allele.…”
Section: Introductionmentioning
confidence: 94%
“…With regard to AAI attachment, there is evidence that early experiences are systematically related to variations in adult state of mind with respect to attachment (Haydon, Collins, Salvatore, Simpson, & Roisman, 2012; Waters, Merrick, Treboux, Crowell, & Albersheim, 2000). Although, in the past, the attachment style literature has been criticized for its dearth of empirical evidence for developmental origins (e.g., Belsky, 2002), recent longitudinal studies have provided compelling evidence for developmental antecedents of adult attachment style (Dinero, Conger, Shaver, Widaman, & Larsen-Rife, 2008; Fraley, Roisman, Booth-LaForce, Owen, & Holland, 2013; Salo, Jokela, Lehtimäki, and Keltikangas-Järvinen, 2011; Zayas, Mischel, Shoda, & Aber, 2011). For example, Fraley et al found that individual differences in attachment style at age 18 were prospectively predicted by variation in the quality of the early caregiving environment, social competence, and the quality of peer relationships.…”
Section: Remaining Issues and Unresolved Questionsmentioning
confidence: 99%
“…Developmental approaches to close relationships, such as attachment theory [1,2,3], assume that these individual differences are reflections of the way in which people's personalities have become organized by interpersonal experiences over the course of their lives, beginning with their earliest relationships. Indeed, a growing body of developmentally informed research has begun to explore the ways in which early experiences are manifested in close relationships and interpersonal functioning [4][5][6][7][8][9][10][11][12]. Research has shown, for example, that early attachment experiences are associated with the ways in which people resolve conflict and regulate emotion in their romantic relationships [13,14].…”
Section: Introductionmentioning
confidence: 99%